Trends in income inequality in the European Union: implications for health inequalities - Marta Pascual; David Cantarero; Jose Maria Sarabia (European Regional Science Association (ERSA), 2004)
The comparative analysis of income inequality across countries has acquired increasing importance in recent years. This paper is divided in two parts. The first one is focused on the analysis of income inequality in the European Union. To carry out this task, we use different models based on Lorenz curves and quantiles functions and different equivalence scales. The European Community Household Panel Data are used. The second part of the paper is focused on explaining the differences in income and health inequalities across European countries. In particular several hypotheses concerning the economic determinants of health inequalities are studied. KEY WORDS Income inequality, Lorenz curves, quantile functions, equivalence scales, European Community Household Panel, health inequalities
Keywords: 330; Income inequality; Lorenz curves; quantile functions; equivalence scales; European Community Household Panel; health inequalities